Inclusion of students with disabilities and Educational Guidance in Italy: a comprehensive analysis of the 2022 guidelines and recent legislative developments - Della Volpe, Valentina (European Scientific Journal, ESJ, 2024)
The educational guidance and inclusion practices in Italian schools have undergone significant evolution over the last few years. Recent legislative updates emphasize equity, inclusion, and personalized educational paths, acknowledging the diverse backgrounds, languages, and abilities of students. The 2022 guidelines for school guidance, introduced within the framework of the National Recovery and Resilience Plan (PNRR), further underline the importance of creating an inclusive educational environment. This article explores the most recent regulations from 2020 alongside the latest Eurydice reports to analyze their implications for inclusive education, the role of pedagogical frameworks, and strategies to advance equity and accessibility in schools.